HUBUNGAN ANTARA BODY SHAMING DENGAN KEPERCAYAAN DIRI PADA SISWA DI YAYASAN PERGURUAN KARYA PEMBANGUNAN DELITUA TAHUN 2026 - Eva Sariulina Sianturi; Dina Hidayati Hutasuhut; Nur Asyah; Vinda Chairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Body shaming is an act of criticizing a person's physical appearance that can affect self-confidence, particularly among adolescents who are in the stage of developing their self-identity. However, not all adolescents who experience body shaming suffer a decline in self-confidence. This study aims to determine the relationship between body shaming and self-confidence among adolescents. It employs a quantitative research method with a correlational design. A sample of 15 tenth-grade students from the Karya Pembangunan Deli Tua Educational Foundation (2026) was selected using purposive sampling. The instruments used were questionnaires measuring body shaming and self-confidence, both of which had undergone validity testing. The results showed a significance value (p) of 0.001 (p < 0.05) and a correlation coefficient (r) of 0.259. Based on the correlation coefficient, it can be concluded that higher levels of body shaming are associated with lower levels of self-confidence among students at the Karya Pembangunan Deli Tua High School; conversely, lower levels of body shaming are associated with higher levels of self-confidence. This interpretation is based on the correlation coefficient guidelines provided by Sugiyono (2022). These findings indicate that adolescent self-confidence is influenced not only by negative experiences but also by other factors, such as self-acceptance and social support.